Literature Review: A Comparative Analysis of Cooling Methods for Enhancing Solar Panel Efficiency - Syahrian, Nur Mutiara; Faroja, Anas; Rusdianasari (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
Overheating can significantly reduce the efficiency and power output of solar panels, leading to the development of various cooling techniques. This paper compares four cooling methods: heatsink with fan, fin heatsink, water cooling, and floating solar panels. The study evaluates these methods based on temperature reduction, cooling efficiency, electrical performance, and practical considerations. Active systems, like water cooling and heatsink with fan, showed higher performance improvements but required more resources and were more complex to operate. On the other hand, passive systems such as fin heatsink, and floating panels offered simpler and more sustainable solutions with moderate efficiency gains. This review highlights the balance between efficiency, sustainability, and practicality, providing valuable insights for choosing the best cooling method for solar panels. The findings also point to future opportunities for advancements through hybrid systems and new materials to enhance performance and sustainability in solar energy systems.